2021
DOI: 10.1016/j.resourpol.2021.102163
|View full text |Cite
|
Sign up to set email alerts
|

Is gold favourable than bitcoin during the COVID-19 outbreak? Comparative analysis through wavelet approach

Abstract: The novel coronavirus (COVID-19) has tremendously oscillated the global financial markets. Consequently, investors feel pressured to find safe-haven investments during the pandemic crisis. Numerous studies have evaluated bitcoin's safe-haven properties during the COVID-19; however, the present study considered gold as a potential safe-haven for investors of renowned stock markets of Asia, Europe, and the US. The present investigation computed the ratio of gold to bitcoin (Gold_Bitcoin) and compared the safe-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…This study showed that the number of cases, social distancing and other lockdown practices hurt stock markets and economic activities. Moreover, other papers in the extant literature confirmed similar results (Liu et al, 2020 ; Shehzad, Bilgili, et al, 2021 ; Zaremba et al, 2021 ; D. Zhang, Hu, & Ji, 2020 ).…”
Section: A Literature Review and The Variable Selectionsupporting
confidence: 63%
“…This study showed that the number of cases, social distancing and other lockdown practices hurt stock markets and economic activities. Moreover, other papers in the extant literature confirmed similar results (Liu et al, 2020 ; Shehzad, Bilgili, et al, 2021 ; Zaremba et al, 2021 ; D. Zhang, Hu, & Ji, 2020 ).…”
Section: A Literature Review and The Variable Selectionsupporting
confidence: 63%
“… Śmiech and Papież (2017) argue that gold is a feeble hedge for stocks. Similar results are reported by Shehzad et al (2021a) .…”
Section: Resultssupporting
confidence: 92%
“…For example, Long et al (2021) compare the safe-haven properties of Bitcoin and gold during the COVID-19, but they apply the NARDL model only considering the static aspect. Some scholars consider the dynamic research based on the dynamic conditional correlation model ( Chemkha et al, 2021 ) or wavelet approach ( Shehzad, Bilgili, Zaman, et al, 2021 ), but they focus on the hedge for major stock market. They do not take into account the impact on the oil market.…”
Section: Literature Reviewmentioning
confidence: 99%